Penentuan Dan Pengembangan Kompetensi Inti Kabupaten Bekasi - Rahmat Nurcahyo; Farizal Farizal; Edwin Stiadi; Saparudin Saparudin (Jurnal Teknik Industri, 2012)
Development of a region is a vital issue for the survival of the area. One way for development of a region is based on core competence. This research discusses the core competence of Bekasi region for development. This research methodsare Analytic Hierarchy Process and Interpretive Structural Modeling. Results from this research is a road map model for Bekasi region development, based on small and medium enterprises in food and beverage industry.